STRUKTUR GERAK TARI BESAGU AYU SUKU DAYAK KANTU’ DI DESA BIKA HULU KABUPATEN KAPUAS HULU - Darmanto, Jusnarso; Fretisari, Imma; Sanulita, Henny (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
Abstrak: Penelitian ini dilatar belakangi keinginan peneliti untuk menganalisis gerak pada Tari Besagu Ayu Suku Dayak Kantu’. Tujuan penelitian ini mendeskripsikan struktur gerak tari Besagu Ayu dengan gambar agar jelas dan menganalisis gerak dan struktur gerak tari Besagu Ayu. Metode yang digunakan adalah deskriptif analisis dengan bentuk kualitatif, melalui pendekatan etnokoreologi. Data penelitian ini adalah observasi, wawancara, dan dokumentasi dari para seniman sebagai narasumber. Analisis struktur gerak tari Besagu Ayu dengan empat ragam gerak yaitu gerak Pencak, gerak Sirang 1, gerak Sirang 2, dan gerak Ansing-ansing yang dianalisis berdasarkan motif gerak, frase gerak, kalimat gerak, dan gugus gerak. Hasil penelitian ini diharapkan dapat dijadikan sebagai materi ajar pelajaran Seni budaya dan Ketrampilan (seni tari) dengan menggunakan metode pembelajaran imitasi gerak tari pada siswa SMP di sekolah. Kata Kunci : Struktur Gerak, Tari Besagu Ayu, Dayak Kantu’, Kapuas Hulu. Abstract: The background of in this research is about researcher interest to know about uniqueness ofBesagu Ayu Dance Dayak Kantu’ Etnic. In this study used etnokoreology approach.Refrence of data in Besagu Ayu dance that exhibited by expert and some other artist who know the history of Besagu Ayu dance from the informant who understand about Besagu Ayu dance in Bika Hulu. Data of research is structure movement Besagu Ayu dance in Bika Hulu that have relation with part of dance show, there arethe frist part, in the middle and in the last of dance show. Techniques of data collection are observation, interview, and documentation technique, the technique of data validity testing is extention observation and triangulation technique. Analysis technique is used analys and interpret koreography that have relation with the Structure Of Besagu Ayu Dance Dayak Kantu’ Etnic In Bika Hulu Village Kapuas Hulu District,make a disscusion analysis result with first supervisor and second supervisor than make a conclude the result of research so that we can get description about purpose of variety movement in Structure Of Besagu Ayu Dance Dayak Kantu’ Etnic In Bika Hulu Village Kapuas Hulu District. The result of this research are : 1) structure of koreo Besagu Ayu with three part there are the first part the middle and in the last of dance show.2) plane the result of researc whit curiculum as a teaching material of cultural art lesson (seni tari) with use imitation learning methode of dance in junior high school.Suggestion for the young generations : to keep preserve and to keeping culture especially in Kalimantan Barat, beacause the culture is a nation identity. Keywords: The Structure Dance Of Besagu Ayu, Dayak Kantu’, Kapuas Hulu.